The effect of Library-Assisted Instruction (LAI) on reading ability and reading attitude of elementary school students in Indonesia - Hee Jeong Na; I Nyoman Sudana Degeng; Punaji Setyosari; Dedi Kuswandi; Hyouk Joo Han (Universitas Negeri Malang, 2025)
The purpose of this study is to verify the effect of Library-Assisted Instruction on reading ability and reading attitude. The study was conducted on Indoneia’s elementary school second grade. The Library-Assisted Instruction program was developed as a textbook for second grade of the integrated curriculum and was implemented eight times. The reading ability and reading attitude evaluation tool developed in Korea was modified and used for the Indonesian situation. As a result of analyzing the data collected during the pre- and post-test of reading ability and reading attitude using SPSS Statistics 26, the experimental group in which the teacher librarian and the teacher collaborated to participate in the Library-Assisted Instruction to which subject-related reading was applied showed a statistically significant difference in reading ability and reading attitude compared to the control group. Through these research results, it was verified that Library-Assisted Instruction effective for reading ability and reading attitude.